2021
DOI: 10.1002/14651858.cd008754.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Memory rehabilitation for people with multiple sclerosis

Abstract: Memory rehabilitation for people with multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 158 publications
0
18
0
1
Order By: Relevance
“…The treatment of cognitive impairment in MS is an important unmet need. While cognitive rehabilitation has been proven to be effective in improving cognitive performance in MS [7][8][9], studies with larger sample sizes, inclusion of patients with progressive disease, assessment of the effects on daily life and long-term follow-up data are still lacking [6]. Furthermore, research in the elderly indicates that combined cognitive-motor rehabilitation may be more effective than single cognitive or motor training [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of cognitive impairment in MS is an important unmet need. While cognitive rehabilitation has been proven to be effective in improving cognitive performance in MS [7][8][9], studies with larger sample sizes, inclusion of patients with progressive disease, assessment of the effects on daily life and long-term follow-up data are still lacking [6]. Furthermore, research in the elderly indicates that combined cognitive-motor rehabilitation may be more effective than single cognitive or motor training [23].…”
Section: Discussionmentioning
confidence: 99%
“…Some aspects of the trial need clarification. First, we have chosen not to include a passive control group, since the effectiveness of cognitive rehabilitation in multiple sclerosis has already been proven [7][8][9], and the goal of this study is to evaluate whether a combined cognitive-motor training is more effective than single cognitive or motor training in improving cognitive performance. Second, our primary outcome measure is the digit span backwards, a measure of working memory, since the cognitive part of our training programme is focused on working memory improvement and studies have shown that improvement of cognitive performance seems to be limited to the functions that were trained [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6,27,28 For example, a recent Cochrane Review of 44 memory rehabilitation interventions evaluated in randomised controlled trials in MS found that patients who received memory rehabilitation reported better memory functioning and quality of life relative to those who did not receive memory rehabilitation. 29 A number of recent clinical reviews and guidelines about cognitive rehabilitation in MS are available that can be used to guide care and treatment planning. 4,6,7,10 It is important to note that other 'invisible' MS symptoms (eg fatigue, depression, pain, sleep difficulties) can have an adverse impact on cognitive functioning and therefore may need to be addressed to optimise the outcome of targeted cognitive rehabilitation interventions.…”
Section: Next Steps: Choosing Between the Effective Cognitive Rehabil...mentioning
confidence: 99%
“…(19) In relation to memory-related interventions (activities necessary to improve patient independence and performance of daily activities), 44 studies of a total of 2714 patients found that memory rehabilitation improved functioning and quality of life, although there was no effect in relation to improvement in activities of daily living or decreased anxiety. (20)…”
Section: Multiple Sclerosis Drug Analysismentioning
confidence: 99%